Service orientation in transitional economies: Analysis of critical service factors in two Slowenian banks compared to the USA - Samo Bobek; Monty L. Lynn; Richard S. Lytle (Journal for East European Management Studies, 1998)
Service quality, and the service-oriented practices that create that quality, have been shown to yield competitive advantage to firms in developed and mature markets. The role that service-driven practices play in transitional economies, however, has not been tested. In this study, the SERVOR scale, a measure of organizational service-orientation, was analyzed from 105 employees in two Slovenian banks-one which is a newly established private bank and the other which is a large, older previous state-supported bank. Results indicate that the private bank is more service-oriented in its approach to the marketplace. – – Es hat sich erwiesen, daß Dienstleistungsqualität und dienstleistungsorientierte Verfahrensweisen, welche diese Qualität hervorbringen, Wettbewerbsvorteile für Firmen in entwickelten und etablierten Märkten bedeuten. Die Rolle, die dienstleistungsorientierte Praktiken in Wirtschaftssystemen spielen, welche sich im Transformationsprozeß befinden, wurde jedoch noch nicht untersucht. In der vorliegenden Studie wurde der SERVOR-Maßstab, ein Instrument zur Messung der Dienstleistungsorientierung einer Organisation, von 105 Angestellten in zwei slowenischen Banken analysiert. Eine der Banken ist eine neu gegründete private Bank, die andere eine große, ältere, früher staatlich unterstützte Bank. Die Ergebnisse zeigen, daß die private Bank einem stärker dienstleistungsorientierten Ansatz folgt.
Keywords: 650